2017
DOI: 10.1016/j.yjmcc.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of IGF-1 receptors and Akt signaling by systemic hyperinsulinemia contributes to cardiac hypertrophy but does not regulate cardiac autophagy in obese diabetic mice

Abstract: Autophagy plays an important role in the maintenance of normal heart function. However, the role of autophagy in the inulin resistant and diabetic heart is not well understood. Furthermore, the upstream signaling and the downstream targets involved in cardiac autophagy regulation during obesity and type 2 diabetes mellitus (T2DM) are not fully elucidated. The aim of this study was to measure autophagic flux and to dissect the upstream and downstream signaling involved in cardiac autophagy regulation in the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…In order to study cardiac function independently of the effect of obesity [17], hyperinsulinemia [18] and high-glycemic load [19], we selected animals within each sex group that had similar body weight as well as normal insulin and FBG levels (Fig 1). Only one male in the Chow group had borderline high FBG value (6.4 mmol l -1 , compared with 5.6 mmol l -1 threshold).…”
Section: Resultsmentioning
confidence: 99%
“…In order to study cardiac function independently of the effect of obesity [17], hyperinsulinemia [18] and high-glycemic load [19], we selected animals within each sex group that had similar body weight as well as normal insulin and FBG levels (Fig 1). Only one male in the Chow group had borderline high FBG value (6.4 mmol l -1 , compared with 5.6 mmol l -1 threshold).…”
Section: Resultsmentioning
confidence: 99%
“…26 A study in db/db mice suggested that systemic hyperinsulinemia contributed to cardiac hypertrophy, which could be blocked by the deletion of insulin-like growth factor-1R. 27 Continuous administration of insulin for 7 weeks using osmotic pumps increased LV mass and relative wall thickness in rats. 28 In isolated rat cardiomyocytes, insulin treatment induced cardiomyocyte hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The GH/IGF-1 axis enhances the calcium intracellular and cardiomyocytes contractility. In obesity and type 2 diabetes mellitus (T2DM), IGF-1 can induce cardiomyocytes hypertrophy through overactivity of growth pathway [66].…”
Section: Insulin Growth Factor 1 (Igf-1)mentioning
confidence: 99%